Effect of Recruitment Activities on Performance of Hotels in Anambra and Delta States of Nigeria - Gloria Ndidi Iseh (CV Projurnal Mitra Publikasi, 2025)
This study investigated the impact of recruitment activities on hotel performance in Anambra and Delta States, Nigeria. A multi-stage sampling technique was used: two states were purposively chosen, followed by the selection of 30 functional hotels. Employees were randomly sampled across five departments including housekeeping, front office, food and beverages, maintenance and engineering, and security which totaling 2,250 workers. Using Taro Yamane’s formula, 321 full-time staff were sampled. Data were analyzed using Pearson product-moment correlation. Results showed a significant (p<0.01) relationship between recruitment activities and sales volume, cost control, and labour turnover. Effective recruitment enhances performance by ensuring alignment between employees and organizational needs. Selecting suitable candidates improves productivity, efficiency, and retention, fostering workforce stability. The study recommends that hotels strengthen their recruitment processes through rigorous screening, structured interviews, and competency-based assessments to ensure candidates’ skills and values fit organizational requirements. Strategic recruitment practices will enhance overall hotel performance and competitiveness in the hospitality industry.